Airborne fungal spore content in the atmosphere of the city of La Plata, Argentina - Mallo, Andrea Cecilia (2011)
The aim of this paper is to present the first aeromycological study of the atmosphere of the city of La Plata. Air samples were taken using a Hirst-type volumetric spore trap sampler (Lanzoni, VPPS 2000) for a period of a year (July 2000–June 2001). Seventy-nine morphological types of spores belonging to the Phyla Myxomycota, Zygomycota, Oomycota, Ascomycota, Basidiomycota, as well as anamorphs of Higher Fungi were identified. A total of 171670.21 spores were recorded, with a daily mean of 540 spores/m³. The spores were present throughout the year the study was carried out. However, there was a wide daily fluctuation in the concentration values with a tendency toward an increase during the summer months. The fungal spores were classified in three categories: abundant, having five spore types; moderate having 12 types; and low, with 62 morphological types which represent 67.2, 24.2, and 8.6%, respectively. The most representative taxa were Cladosporium cladosporioides, Leptosphaeria, Cladosporium herbarum, Coprinus, and Agaricus, the first two taxa having a high frequency during the year of study. This scientific research reveals a great diversity of morphological types in this outdoor environment, showing a strong dominance of the Imperfect Fungi, whose components have seasonal rates. By this study, the first aeromycological profile of an urban center of Argentina has been portrayed, and new information on the field of aeromycology in the country has been provided.